2021
DOI: 10.1007/s00127-021-02178-7
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and lifestyle factors associated with mental health problems among Mongolian elementary school children

Abstract: Purpose Lifestyle factors of children and adolescents’ mental health problems are an emerging health issue in low- and middle-income countries (LMICs). However, there is a lack of studies on lifestyle factors in LMICs. This study examined the socioeconomic and lifestyle factors associated with mental health problems among school-age children in Mongolia. Methods A population-based cross-sectional survey was conducted among 4th-year students at public elementary schools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In this sense, a previous study showed that high ST and bad food habits were related with poorer mental health; likewise, this study reported that physical fitness dimensions were positively linked with the absence of body image dissatisfaction [ 14 ]. Likewise, a cross-sectional study conducted in children indicated that excessive ST was linked with a high risk of internalizing and externalizing mental health problems; therefore, the authors concluded that it is fundamental to develop healthy lifestyle interventions [ 44 ]. In addition, a systematic review which examined the longitudinal relation between ST and mental health reported that recreational ST was negatively linked with psychological wellbeing [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, a previous study showed that high ST and bad food habits were related with poorer mental health; likewise, this study reported that physical fitness dimensions were positively linked with the absence of body image dissatisfaction [ 14 ]. Likewise, a cross-sectional study conducted in children indicated that excessive ST was linked with a high risk of internalizing and externalizing mental health problems; therefore, the authors concluded that it is fundamental to develop healthy lifestyle interventions [ 44 ]. In addition, a systematic review which examined the longitudinal relation between ST and mental health reported that recreational ST was negatively linked with psychological wellbeing [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The explanatory variables in the logistic regression analysis included gender, living area, family structure, maternal education, household income, sleep, physical activity, and screen time. Additionally, our study was conducted in the Gobi-Altai province, whereas this study focused on the 4th grade students in one district of Ulaanbaatar city [15].…”
Section: Discussionmentioning
confidence: 99%
“…The associations between PPD and all independent variables were analyzed using a multivariate logistic regression model, after which the adjusted odds ratio (OR) was calculated. The statistical significance threshold was set at a p-value of <0.05 (i.e., 5% alpha) [ 21 ]. The analysis was performed using SPSS version 22.0 (IBM Corp., Armonk, NY, USA), considering the applicable RISKESDAS weights, strata, and primary sample units following the RISKESDAS survey design, as previously reported [ 18 ].…”
Section: Methodsmentioning
confidence: 99%